Stakeholder housing : a third way - Brown, Tim, 1954 May 13- (Pluto Press, 1999)
Annotation The Labour Housing Group (LHG) has been at the forefront of the housing debate in the UK for the past decade. In this groundbreaking study, the LHG explores how housing can contribute to New Labour's "Third Way" agenda of addressing social exclusion by involving stakeholders, balancing state and market interests, and addressing devolution. The distinguished contributors to this volume - ranging from members of the Labor government to well-known practitioners and academics - examine ways in which the much-touted Third Way can be translated from rhetoric into real and meaningful practice that has a positive impact on the lives of the community. The debate over the provision of adequate housing for all is scrutinized from a variety of perspectives, such as that of consumer, of provider, and of regulator. The authors make explicit the links between housing, health and the environment; set out a new agenda for housing; and explore what the Third Way might mean for housing stakeholders and those working in or studying housing and social policy